Adaptive deterministic approach for optimized sizing of high-energy battery system applied in electric-powered application. (1st March 2022) - Han, Seungyun; Kobla Tagayi, Roland; Kim, Jaewon; Kim, Jonghoon
Highlights: Nonlinear characteristics of lithium-ion battery are modeled with EECM and Peukert's law. Load profiles are analyzed by energy and power demands and fluctuation characteristics. Ageing effects of operating condition is considered by the fluctuation feature of load profile. Adaptive deterministic approach is used to obtain optimal size of the battery system. Proposed battery system size optimization is applied and verified in EVs and PV generators. Abstract: For achieving decarbonization globally, most electric applications, such as electric vehicles (EVs) and photovoltaic (PV) generators, are moving toward the use of eco-friendly and renewable energy sources. Currently, one of the most utilized energy storage devices is the lithium-ion battery, which has various advantages than other systems. In addition, a lithium-ion battery presents nonlinear characteristics during operation. Therefore, these features should be considered in the design of battery systems with load requirements. In this paper, energy and power characteristics were analyzed in terms of battery system size in relation to EVs and PV generators. If a battery system is designed to supply power less than the energy demand, it will be utilized beyond the designed and safety range, and there will be generation of waste residual energy. However, if a battery system is designed to supply power more than the demand, additional investment and maintenance cost will be incurred to setup the battery system. Thus, this paper proposes an optimal sizing method for a lithium-ion battery system considering its nonlinear features using Peukert's law and the analyzed load conditions. To obtain the ideal size of the battery system, an adaptive deterministic approach is implemented. After determining the optimal battery system size, a simulation of the battery system with a load profile is conducted to verify that it satisfies all constraints of the battery system.